Can infrared thermography be used to monitor fatigue during exercise? A case study - Vedran Hadžić; Brane Širok; Aleš Malneršič; Milan Čoh (Elsevier, 2019)
Background: Infrared thermographic imaging (IRTG) is a safe and reliable technology used to monitor skin temperature. The main aim of our study was to evaluate the relationship between skin temperature changes and muscle fatigue in order to answer the main research question if IRTG can be used to monitor muscle fatigue. Methods: This was a case study performed on a 23-year-old trained middle distance runner. After warm-up the subject was exercising on the dynamometer for 7.5 min at 120°/s performing only concentric contractions of quadriceps. At the same time IRTG recording of both (exercising and non-exercising) quadriceps was performed. Results: A correlational analysis that was performed in order to quantify the relationship between power and temperature change over time has shown that there is a significant negative correlation between skin temperature increase and power decrease (r = −0.543, p = 0.036) of exercising quadriceps. In linear regression model the exercising quadriceps power could be predicted from skin temperature. No such relationships were noted for the non-exercising limb that served as a control. Conclusion: We believe that correlation between skin temperature change and muscle power output as described in this case study deserves further analysis on the larger sample including subjects of the different ages, health status, and physical abilities in order to create a new tool for monitoring the muscle fatigue. Keywords: Correlation, Fatigue, Isokinetic, Quadriceps, Strength, Thermographic imaging